Benefits of exercise for children and adolescents with autism spectrum disorder: a systematic review and meta-analysis - Jia, Mingyuan; Zhang, Jia; Pan, Jianhua; Hu, Fengting; Zhu, Zhipeng (Frontiers in Psychiatry, 2024)
Background: Numerous experimental studies have shown that exercise can serve as an intervention with beneficial effects on children and adolescents with autism. However, a systematic review on the specific areas affected has not been conducted. Methods: Preliminary research sources were obtained by searching four databases, and two researchers independently screened the literature that met the study criteria. The study was conducted under the guidelines of the Cochrane Handbook for Systematic Reviews of Interventions. Results: 37 studies were included in the final analysis, of which 9 studies were quantitatively synthesized and 28 studies were qualitatively analyzed. Exercise interventions have positive effects on motor performance, cognitive function, individual and social relationships, behavioral problems, physical health, and brain function in children and adolescents with autism. The results of the meta-analysis indicate that exercise can effectively improve social skills [SMD=-0.53, 95%CI (-0.76, -0.3), P=0.000]. Conclusions: Long-term, regular, chronic exercise is beneficial for children and adolescents with autism, particularly in the area of social skills.